Penanda Molekul DNA Mikrosatelit untuk Karakterisasi Bibit Jamur Kuping (Auricularia polytricha [Mont.] Sacc.) - I Nyoman Pugeg Aryantha; Yuniar Mulyani; Rahmat Ariffudin (Jurnal Matematika & Sains, 2008)
This study aims to find out a method of spawn characterization for wood ear mushroom (A. polytricha [Mont.] Sacc.)based on microsatellite DNA marker. Four strains of wood ear mushroom cultivated in several regions of Java i.e AUC(West Java), AUCN (Central Java), AUP (West Java) and AUT (West Java) were evaluated. A pair of designed primers(5â -GGGAAAGTGATCCCATCTT-3â and 3â-AGTTGTGGGAACATCGAACT-5â) was able to amplify microsatelliteDNA from those four strains of wood ear mushroom. Strains AUC, AUCN and AUP share the same positions (2 loci) ofmicrosatellite motive (TC)n with PCR products of 212 and 201 bp, while the same motive for strain AUT was found atdifferent loci with PCR products of 127, 108, and 96 bp. The same motive was also found at another locus of strainAUC and AUP with a PCR product of 228 bp. Another different locus with a PCR product of 85 bp also gave positiveamplification result for strain AUC. The data on macroscopic characters (mycelial growth rate and quality, fruitingpercentage and mushroom yield) revealed that AUC, AUCN and AUP are good strains, while AUT is bad strain.Overall, there is a good correlation between molecular (microsatellite DNA) patterns and macroscopic data on mycelialgrowth rate and quality, as well as flushing percentage and mushroom yield. Therefore, microsatellite DNA motive of(TC)n can be adopted for spawn characterization of wood ear mushroom.